ANALISIS PERAN LEMBAGA ADAT SEBAGAI MITRA PEMERINTAH DESA DALAM PELESTARIAN BUDAYA DI DESA (Studi Kasus Desa Ulu Danau Kecamatan Sindang Danau Kabupaten Ogan Komering Ulu Selatan) - Adib Nailuzuam; Eva Susanti; Herni Rahmayanti (PT. Hasba Edukasi Mandiri, 2026)
The Village Customary Institution is an institution that carries out customary functions and forms part of the original structure of the village, established and developed based on the initiative of the village community, as stipulated in Law of the Republic of Indonesia Number 6 of 2014 concerning Villages. This study aims to analyze the role of the Village Customary Institution as a partner of the village government in preserving culture in Ulu Danau Village, Sindang Danau District, South Ogan Komering Ulu Regency. This research employed a descriptive qualitative method. The study used role theory consisting of interpersonal roles, informational roles, and decisional roles, with sub-indicators including preserving, developing, and fostering customary values. The findings indicate that the preservation of the indigenous culture in Ulu Danau Village has been successfully achieved. The interpersonal, informational, and decisional roles performed by the Village Customary Institution in preserving, developing, and fostering customary values have been implemented effectively. The study recommends that the Village Government and the Village Customary Institution of Ulu Danau place greater emphasis on education and training to support the preservation, development, and strengthening of customary values in accordance with the demands of modernization.